PENGGUNAAN ALAT PERAGA DARI BAHAN BEKAS DALAM MENJELASKAN SISTEM RESPIRASI MANUSIA DI MAN SAWANG KABUPATEN ACEH SELATAN - Abdullah Abdullah; Wati Oviana; Husnil Khatimah (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2011)
Model are a physical medium used to deliver educational content educational materials that can stimulate students to learn. One of the model that can be used in learning, especially learning the human respiratory system are the model of scrap materials. The research was conducted in South Aceh regency Sawang MAN. The purpose of this study was to determine the increase in academic achievement and student responses to the use of model used ingredient in explaining the human respiratory system in Sawang MAN South Aceh regency. The subject of this study was all students in grade XI IPA-1 MAN Sawang South Aceh district, school year 2010/2011. The design of this study is Classroom Action Research (PTK). Instruments used in this study is Teacher Observation Sheet (LOG), Student Observation Sheets (LOS), test (pre-test and post-test), and questionnaire responses of students. Based on the results of data analysis, it is known that an increase in student achievement based on the thoroughness of student learning both individually and classical indication of the success of student learning based on test results (pre-test and post-test), t test analysis, as well as the positive response of students towards learning with use props material scrap materials on the human respiratory system. Teacher and student activities are categorized either as a whole.